A Grid-Inspired Mechanism for Coarse-Grained Experiment Execution - Leye, S.; Himmelspach, J.; Jeschke, M.; Ewald, R.; Uhrmacher, A.M. (2008 12th IEEE/ACM International Symposium on Distributed Simulation and Real-Time Applications, 2008)
Stochastic simulations may require many replications until their results are statistically significant. Each replication corresponds to a standalone simulation job, so that these can be computed in parallel. This paper presents a grid-inspired approach to distribute such independent jobs over a set of computing resources that host simulation services, all of which are managed by a central master service. Our method is fully integrated with alternative ways of distributed simulation in JAMES II, hides all execution details from the user, and supports the coarse-grained parallel execution of any sequential simulator available in JAMES II. A thorough performance analysis of the new execution mode illustrates its efficiency.